A new species of Hamodes Guenée, 1852 (Lepidoptera: Erebidae) from China - Zhang, Yu-Long; Wei, Fuhong; Fan, Xiaoling; Wang, Min (Zootaxa, 2023)
A new species of the genus Hamodes Guenée, 1852, Hamodes zhipengi sp. nov. is described and illustrated from China. The species resembles H. pseudobutleri Wei & Wang, 2019 but differs in wings ground colour; and male genitalia with differently shaped valvae, ampullae and armature of vesica. DNA barcode of the new species and relatives are deposited in GenBank. The holotype is deposited in the Department of Entomology, College of Plant Protection, South China Agricultural University, Guangzhou.